CHARACTER ANALYSIS OF JOE GOLDBERG IN CAROLINE KEPNES’ YOU AND HIDDEN BODIES NOVELS - Diyan Puspa Wahyuni; Singgih Daru Kuncara; Indah Sari Lubis (Prosiding Seminar Nasional Bahasa, Sastra, dan Seni (Sesanti), 2021)
This research was aimed at analyzing the personality of the main character, Joe Goldberg, in Caroline Kepnes’ You and Hidden Bodies novels. Joe’s personality was analyzed by applying Sigmund Freud’s psychological approach that took a focus on the id, ego, and superego of humans. Character and characterization theory by Kelly Griffith was added in identifying Joe to get a deeper and better grasp of what kind of character he is. As a result of the analysis of the research, it showed that Joe’s id was described through the impulsiveness in his actions, his ego was portrayed through maintaining to have a positive self-image in front of a woman he likes while his superego was depicted through his awareness of having a good moral by doing righteous deeds. However, Joe’s actions and behaviors tend to lean more towards his id, which is the instinct and basic urges of humans to bring pleasures and avoid any painful feelings to protect the individual. Overall, Joe’s id, ego, and superego were depicted through his actions and thoughts throughout the story.